2008
DOI: 10.1021/ac8015467
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption/Ionization-Ion Mobility Separation-Mass Spectrometry Imaging of Vinblastine in Whole Body Tissue Sections

Abstract: During early-stage drug development, drug and metabolite distribution studies are carried out in animal tissues using a range of techniques, particularly whole body autoradiography (WBA). While widely employed, WBA has a number of limitations, including the following: expensive synthesis of radiolabeled drugs and analyte specificity and identification. WBA only images the radiolabel. MALDI MSI has been shown previously to be advantageous for imaging the distribution of a range of drugs and metabolites in whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 25 publications
0
172
0
1
Order By: Relevance
“…For small molecules analysis, two main classes may be distinguished -exogenous drugs and endogenous metabolites. Exogenous drugs have been studied in MALDI-MSI far later than proteins (since 2004) for different targets such as olanzapine (antipsychotic) [85][86][87], imatinib [87], vinblastine [88], and banoxantrone [89] (cancer drugs). Among endogenous metabolites, lipids such as glycerophospholipids and glycosphingolipids or simple lipids like cholesterol, diacylglycerols, or triacylglycerols have been extensively investigated [90].…”
Section: Maldi Mass Spectrometry Imagingmentioning
confidence: 99%
“…For small molecules analysis, two main classes may be distinguished -exogenous drugs and endogenous metabolites. Exogenous drugs have been studied in MALDI-MSI far later than proteins (since 2004) for different targets such as olanzapine (antipsychotic) [85][86][87], imatinib [87], vinblastine [88], and banoxantrone [89] (cancer drugs). Among endogenous metabolites, lipids such as glycerophospholipids and glycosphingolipids or simple lipids like cholesterol, diacylglycerols, or triacylglycerols have been extensively investigated [90].…”
Section: Maldi Mass Spectrometry Imagingmentioning
confidence: 99%
“…[8][9][10] Disease studies such as the fundamental understanding of the biochemistry of neurodegenerative diseases 11,12 or cancer, 13 drug distribution studies 10,14 and forensics, 15,16 among others, also benefit from the information revealed by MSI.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling MSI with preseparation by IMS has allowed marked enhancement of imaging contrast through improved selectivity and signal-to-noise ratio by separating isobaric interferences. MALDI-IM-MSI was shown to expand the dimensionality of data produced, in comparison with traditional MALDI-MSI data sets, for human glioma studies (47 ) and was also used for imaging of the anticancer drug vinblastine in whole body tissues (48 ). Fig.…”
Section: Applications Of Ion Mobility In Proteomics Metabolomics Anmentioning
confidence: 99%